Human rights implementation and compliance : prospects for realising the AU convention on internally dosplayced persons in Uganda - Whittaker, Nicola (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.